Population Density of Foliage Insect Pest on Jujube, Ziziphus mauritiana Lam. Ecosystem - Imtiaz Ahmed Nizamani; M.A. Rustamani; S.M. Nizamani; Shafique Ahmed Nizamani; Muhammad Ibrahim Khaskheli (Journal of Basic & Applied Sciences, 2015)
Jujube, Ziziphus mauritiana L. is the King of arid zone fruits, due to its adaptations to tolerate the biotic and abiotic stresses. However, the occurrence of insect pest is the major threat to reduce the quality and quantity of fruits. The current studies are the first comprehensive evidence on the population density of foliage insect pests evaluated on two different varieties, Golden Gola (susceptible) and White Kherol (resistance) at farmer’s field Tando Qaiser, District Hyderabad during 2007 and 2008. A total of 13 different insect pests which were categorized as major (Ancylis sativa, Euproctis fraterna and Adoretus pallens), minor (Scirtothrips dorsalis, Amrasca biguttula biguttula, Myllocerus discolor, Achaea janata, Agrotis biconica and Aphis gossypii) and occasional (Oxycareous hyalinipennis, Dichromorpha viridis, Tarucus balkanicus and Orgyia postica) based on overall population of two years. The mean population percentage of insect pests indicates the highest percentage for E. fraterna followed by A. pallens, A. biguttula biguttula, M. discolor and S. dorsalis on White Kherol, whereas, Golden Gola was severely infested and showed maximum percentage with A. sativa followed by E. fraterna, S. dorsalis, A. pallens and A. biguttula biguttula. It is concluded that A. sativa, E. fraterna and A. pallens are serious insect pests of jujube. Pest monitoring with direct count and light trap can help to determine the ETL that is most important for the management of various insect pests including these major and minor pest. The present study will hopefully be helpful for management of foliage insect pests of jujube..